2022
DOI: 10.1097/ju.0000000000002293
|View full text |Cite|
|
Sign up to set email alerts
|

Findings in 1,123 Men with Preoperative 68 Ga-Prostate-Specific Membrane Antigen Positron Emission Tomography/Computerized Tomography and Multiparametric Magnetic Resonance Imaging Compared to Totally Embedded Radical Prostatectomy Histopathology: Implications for the Diagnosis and Management of Prostate Cancer

Abstract: Purpose:Multiparametric magnetic resonance imaging (mpMRI) fails to identify some men with significant prostate cancer. Prostate-specific membrane antigen positron emission tomography/computerized tomography (PSMA PET/CT) is recommended for staging of prostate cancer, but its additional benefit above mpMRI alone in local evaluation for prostate cancer is unclear. The study aim was to evaluate the ability of mpMRI and PSMA PET/CT individually and in combination, to predict tumor location and Gleason score ≥3+4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…A retrospective analysis of men with low to intermediate-risk PCa found that PSMA identi ed GG³ 2 malignancies more frequently than GG 1 with sensitivity of 88% versus 18% (6). This is further supported by Raveenthiran et al that retrospectively analysed 1123 men and identi ed 92% of csPCa by combining mpMRI and (68)Ga-PSMA PET/CT (22). These ndings were con rmed in the prospective multicentre trial (PRIMARY trial) (23).…”
Section: Discussionmentioning
confidence: 56%
“…A retrospective analysis of men with low to intermediate-risk PCa found that PSMA identi ed GG³ 2 malignancies more frequently than GG 1 with sensitivity of 88% versus 18% (6). This is further supported by Raveenthiran et al that retrospectively analysed 1123 men and identi ed 92% of csPCa by combining mpMRI and (68)Ga-PSMA PET/CT (22). These ndings were con rmed in the prospective multicentre trial (PRIMARY trial) (23).…”
Section: Discussionmentioning
confidence: 56%
“…A retrospective analysis of men with low to intermediate-risk PCa found that PSMA identified GG≥ 2 malignancies more frequently than GG 1 with sensitivity of 88% versus 18% [ 6 ]. This is further supported by Raveenthiran et al that retrospectively analysed 1123 men and identified 92% of csPCa by combining mpMRI and (68)Ga-PSMA PET/CT [ 22 ]. These findings were confirmed in the prospective multicentre trial (PRIMARY trial)[ 23 ].…”
Section: Discussionmentioning
confidence: 67%
“…Finally, as technology improves, so too will the criteria for FT selection and follow‐up. New technologies including PSMA PET/CT can potentially improve selection for FT. PSMA PET/CT can identify tumours not found on MRI [ 30 ]. With concordance between MRI, PSMA PET/CT and biopsy histology, there will be more confidence for clinicians that there is no undiagnosed significant out‐of‐field malignancy at diagnosis.…”
Section: Discussionmentioning
confidence: 99%